2018
DOI: 10.15666/aeer/1606_81198129
|View full text |Cite
|
Sign up to set email alerts
|

Response of Some Plant Species Towards the Allelopathy of Two Types of Chickpea (Cicer Arietinum L.) Seed Extracts

Abstract: Ashti et al.: Response of some plant species towards the allelopathy of two types of chickpea (Cicer arietinum L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…However, it is not clear how the allelopathic activity of chavicol changes among these isoforms. For the allelopathic study in this work, eugenol was chosen as the comparative allelochemical compound to the BE because of the studies of allelopathic activity and the mode of action of eugenol or isoeugenol in several reports [ 20 , 24 , 30 ]. Nevertheless, the most abundant phenylpropanoid in BE was allyl-pyrocatechol diacetate (4-allyl-1,2-diacetoxybenzene), and the allelopathic action of BE might be from this compound.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not clear how the allelopathic activity of chavicol changes among these isoforms. For the allelopathic study in this work, eugenol was chosen as the comparative allelochemical compound to the BE because of the studies of allelopathic activity and the mode of action of eugenol or isoeugenol in several reports [ 20 , 24 , 30 ]. Nevertheless, the most abundant phenylpropanoid in BE was allyl-pyrocatechol diacetate (4-allyl-1,2-diacetoxybenzene), and the allelopathic action of BE might be from this compound.…”
Section: Discussionmentioning
confidence: 99%
“…These secondary metabolic compounds can affect the processes of building and transporting amino acids and thus reduce the rate of protein building [19]. These compounds also reduce the absorption of ions and inhibition the growth process in plant cells by inhibiting protein synthesis [20].…”
Section: Results and Discussion: Proteinsmentioning
confidence: 99%
“…It is suggested that the allelochemicals in fig tree leaves may be released into the soil environment through rain and mist, which can directly or indirectly promote the growth of mint. The allelopathy of plant species is very complex, and the effects of extracts from the same part of the same donor plant on different recipient plants may also be different [63]. Certain plant allelochemicals have hormone-like effects or promote the growth of the recipient plant by changing the hormone composition and concentration of the recipient plant [64].…”
Section: Discussionmentioning
confidence: 99%